Postcolonial Perspectives on the Inclusion of Immigrant Students in Galiza, Spain Perspectivas Postcoloniales sobre la Acogida del Alumnado Inmigrante en Galiza, España. - Cathryn Teasley (Arizona State University, 2008)
This study offers a critical exploration of educational policy in Galiza (or Galicia), Spain, in light of the growing cultural diversity of its population and its own socio-cultural history. By situating schools' "welcoming" (acogida), or reception and inclusion, of immigrant students within a broad, transversal terrain of postcolonial and relational (McCarthy, 1993 and 2005) analysis–one that traverses disciplinary perspectives and national and historical contexts–the main intent is to reflect on specific aspects of the official inclusion policy in order to help transform schooling into a more just and integrative cross-cultural institution. A series of ethnographic observations currently underway in educational communities of the four provinces of Galiza will provide some initial impressions of this policy as seen from the necessary perspectives of practice in schools. Some key questions include: What relevance does the postcolonial perspective have for the educational integration of immigrant students in Galiza? Does the mere development of a postcolonial awareness among teachers and students, as well as a relational understanding of today's world, constitute a potentially transformational, even emancipatory, pedagogical and curricular intervention? It is argued that it does, to the extent that it reveals the assimilationist orientation of integration, in the currently predominant approaches to inclusion or welcoming. Este estudio representa una exploración crítica de la política educativa de Galiza (o Galicia), España, ante la creciente diversidad cultural de su población y ante su propia historia sociocultural. Al situar la "acogida" escolar del alumnado de origen inmigrante dentro de un amplio terreno transversal de análisis postcolonial y relacional (McCarthy, 1993 y 2005)-uno que atraviesa perspectivas disciplinarias y contextos nacionales e históricos-la intención principal es reflexionar sobre determinados aspectos de la política oficial de acogida para poder contribuir a la transformación de la escolarización en una institución intercultural más justa e integradora. Una serie de observaciones etnográficas, en curso de realización en comunidades educativas de las cuatro provincias de Galiza, proporcionarán unas primeras pinceladas de las necesarias perspectivas desde la práctica de esta política. Algunas preguntas clave son: ¿Qué relevancia tiene la perspectiva postcolonial para la integración escolar del alumnado inmigrante en Galiza? ¿El mero hecho de desarrollar una conciencia postcolonial entre profesorado y alumnado, así como una comprensión relacional del mundo actual, constituiría una intervención pedagógica y curricular potencialmente transformadora, incluso emancipadora? Se argumentará que sí, en la medida en que revela la orientación asimilacionista de la integración y de los abordajes, ahora preponderantes, de la inclusión y la acogida.